MEMBANGUN PERILAKU ORGANIZATIONAL CITIZENSHIP APARATUR PAJAK - Ida Bagus Gede Udiyana; Ida Bagus Swaputra; Anak Agung Ngr. Gde. Suindrawan (Forum Manajemen STIMI Handayani Denpasar, 2011)
The Organizational Citizenship Behavior is a work behavior is a work behavior in which the employees are able to conduct their own duties (in role) and also able to conduct other duties outside their own duties (extra role). They will be given compensation in the award system or formal salary indirectly. The nature of Organizational Citizenship Behavior is a work behavior (OCB) is a focus toward the Organizational interest which is show by organizational-interst oriented action rather than self-interst oriented action.